Field Oriented Control of PMSM Supplied by Photovoltaic Source - Mehimmedetsi Boudjemaa; Chenni Rachid (Institute of Advanced Engineering and Science, 2016)
The Permanent magnet synchronous motor (PMSM) is suitable for so much application, such as traction, aeronautics and generally in industrial automated processes. In our work, we will study the application of PMSM in renewable energies especially solar pumping. Our objective is to model the complete system, including the photovoltaic inverter, PMSM and the centrifugal pump under Matlab/Simulink environment. Solar panels generate electrical energy as direct current by direct conversion of solar radiation using semiconductor materials made of monocrystalline, polycrystalline or amorphous silicon. The energy received depends on radiation and on ambient temperature. The permanent magnet synchronous motor (PMSM) is not stable in open loop. To control the PMSM in terms of speed, torque or position, we need to implement vector control.We will establish the field oriented control of a PMSM supplied by photovoltaic source with a focus on their applications in variable speed domain.